Fruit and vegetable intake is inversely associated with severity of inattention in a pediatric population with ADHD symptoms: the MADDY Study. (3rd June 2023) - Robinette, Lisa M.; Hatsu, Irene E.; Johnstone, Jeanette M.; Tost, Gabriella; Bruton, Alisha M.; Leung, Brenda M. Y.; Odei, James B.; Orchard, Tonya; Gracious, Barbara L.; Arnold, L. Eugene
ABSTRACT : Objectives: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder with a U.S. pediatric prevalence of 8–10%. It presents with inattention and hyperactivity/impulsivity; frequently associated with emotional dysregulation (ED) symptoms common in Oppositional Defiant Disorder and Disruptive Mood Dysregulation Disorder. The etiology of ADHD is multi-factorial; symptom severity is associated with diet. This study examines the association of diet quality with ADHD and ED symptoms within a pediatric research cohort. Methods: Baseline data were analyzed for 134 children aged 6–12 years with symptoms of ADHD and ED enrolled in an RCT of multinutrient supplementation. Diet quality was based on Healthy Eating Index-2015 (HEI-2015). ADHD and ED symptoms were assessed using Child and Adolescent Symptom Inventory-5 and Strengths and Difficulties Questionnaire. Linear regression models, adjusting for covariates when necessary, determined association. Results: The mean HEI Total Score of 63.4 (SD = 8.8) was not significantly associated with any outcome symptoms. However, after adjusting for covariates, HEI component scores for total fruit intake (β = −0.158, p = .037) and total vegetable intake (β = −0.118, p = .004) were negatively associated with inattention. Conclusions: The lack of association with total diet quality could be explained by the relatively good baseline diet quality and mild symptom severity in this sample, along with measurement error from dietary intake estimates and relatively small sample size. These findings suggest that dietary intake may impact inattention in children with ADHD and ED: those eating less fruits and vegetables were likely to have more severe symptoms of inattention. Causality is not established by this cross-sectional analysis.